Penerapan Corporate Social Responsibility Sebagai Pilar Menuju Implementasi Good Corporate Governance pada Rumah Sakit PKU Muhammadiyah Surabaya - Andrianto, Andrianto (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2020)
The application of CSR is related to good corporate governance. The implementation of GCG will have a positive impact on the business environment and increase the confidence of stakeholders, especially investors, to the company. This study aims to find out how the application of CSR is a pillar in the direction of good and healthy corporate governance at PKU Muhammadiyah Hospital in Surabaya. This study uses descriptive qualitative research with data collection techniques conducted by semi-structured interviews and documentation on corporate social responsibility and good corporate governance data. The results showed that the PKU Muhammadiyah Surabaya hospital had implemented a CSR program in accordance with the specified program, but in implementing GCG there were values that had not been maximally implemented (the principles of transparency, responsibility and independence)Keywords: Corporate social responsibility, Good Corporate Governance, Transparency,  Responsibility, Independence.